MERCERIZATION PARAMETERS EFFECT ON NATURAL FIBER REINFORCED POLYMER MATRIX COMPOSITE: A REVIEW - M.H., Yussni (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Environmental awareness and depletion of the petroleum resources are among vital factors that motivate a number of researchers to explore the potential of reusing natural fiber as an alternative composite material in industries such as packaging, automotive and building constructions. Natural fibers are available in abundance, low cost, lightweight polymer composite and most importance its biodegradability features, which often called “eco-friendly” materials. However, their applications are still limited due to several factors like moisture absorption, poor wettability and large scattering in mechanical properties. Among the main challenges on natural fibers reinforced matrices composite is their inclination to entangle and form fibers agglomerates during processing due to fiber-fiber interaction. This tends to prevent better dispersion of the fibers into the matrix, resulting in poor interfacial adhesion between the hydrophobic matrix and the hydrophilic reinforced natural fiber. Therefore, to overcome this challenge, fiber treatment process is one common alternative that can be use to modify the fiber surface topology by chemically, physically or mechanically technique. Nevertheless, this paper attempt to focus on the effect of mercerization treatment on mechanical properties enhancement of natural fiber reinforced composite or so-called bio composite. It specifically discussed on mercerization conditions, and natural fiber reinforced composite mechanical properties enhancement.